2019
DOI: 10.1029/2019jf005199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wind Velocity and Nebkha Geometry on Shadow Dune Formation

Abstract: Flow dynamics and sand deposition processes over nebkhas were investigated using computational fluid dynamics simulations, wind tunnel experiments, and field measurements. The computational fluid dynamics simulations showed that nebkha width affects both the elongation and broadening of the wind shadows. The length of the wind shadows decreased as the wind shear velocity increased, following a power function, irrespective of the width and height of the nebkha. There are some uncertainties about the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 69 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…Some similarities are shared with terrestrial "sand shadows" of various types (Bagnold, 1941, pp. 189-191;Hesp, 1981;Hesp & Smyth, 2017;Yang et al, 2019;Zhao et al, 2019), in which a sand deposit extends downwind from a small, nonerodible Journal of Geophysical Research: Planets obstruction (commonly a clump of vegetation, or an isolated rock) in a unidirectional wind regime. The sand deposit is stable only within the aerodynamic protection provided by the upwind obstruction, and shrinks downwind to its termination for two reasons: (1) small, natural variation of wind azimuths around the dominant wind direction create a triangular protection zone that narrows downwind behind the obstacle; and (2) even without small variations of wind azimuth, the boundary layer eventually recovers to normal strength downwind of the obstacle, as demonstrated even in the perfectly unidirectional flows of numerical and wind tunnel experiments (Hesp & Smyth, 2017;Yang et al, 2019).…”
Section: Low Wind Dynamic Pressures Enable Growth Of Large Longitudinmentioning
confidence: 99%
“…Some similarities are shared with terrestrial "sand shadows" of various types (Bagnold, 1941, pp. 189-191;Hesp, 1981;Hesp & Smyth, 2017;Yang et al, 2019;Zhao et al, 2019), in which a sand deposit extends downwind from a small, nonerodible Journal of Geophysical Research: Planets obstruction (commonly a clump of vegetation, or an isolated rock) in a unidirectional wind regime. The sand deposit is stable only within the aerodynamic protection provided by the upwind obstruction, and shrinks downwind to its termination for two reasons: (1) small, natural variation of wind azimuths around the dominant wind direction create a triangular protection zone that narrows downwind behind the obstacle; and (2) even without small variations of wind azimuth, the boundary layer eventually recovers to normal strength downwind of the obstacle, as demonstrated even in the perfectly unidirectional flows of numerical and wind tunnel experiments (Hesp & Smyth, 2017;Yang et al, 2019).…”
Section: Low Wind Dynamic Pressures Enable Growth Of Large Longitudinmentioning
confidence: 99%
“…As a momentous part of the desert ecosystem, nebkha is a kind of wind-driven sedimentary landform developed under the influence of vegetation [10], nebkha, as the linkage between local climate and environment, has the function of soil and water conservation, wind prevention and sand fixation [15]. Previous studies have focused on the distribution of nebkhas [10], its morphological characteristics [17], vegetation diversity and productivity [18], sediment characteristics and supply, and its influencing factors [19][20]. These studies have reported that the formation of nebkhas is mainly controlled by wind intensity, sand sources and vegetation coverage.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, flow–form–sand transport interactions have been studied on various coastal dune landforms, including foredunes (de Winter et al, 2020; Delgado‐Fernandez et al, 2013; Hesp & Smyth, 2016; Hilton et al, 2016; Jackson et al, 2013, 2011; Lynch, Jackson, & Cooper, 2009; Lynch, Jackson, & Cooper, 2010; Petersen, Hilton, & Wakes, 2011; Schwarz et al, 2021; Wakes, Bauer, & Mayo, 2021; Wakes, Hilton, & Konlechner, 2016; Wakes et al, 2010; Walker et al, 2017), foredune scarps (Hesp & Smyth, 2019; Piscioneri, Smyth, & Hesp, 2019), blowouts (Garès & Pease, 2015; Hesp & Walker, 2012; Hugenholtz & Wolfe, 2009; Pease & Gares, 2013; Smyth, Jackson, & Cooper, 2012; Smyth, Jackson, & Cooper, 2013; Smyth et al, 2019; Smyth, Jackson, & Cooper, 2014), parabolic dunes (Anderson & Walker, 2006; Delgado‐Fernandez et al, 2018; Hansen et al, 2009; Smyth et al, 2020; Wakes, 2013), nebkha (Hesp & Smyth, 2017; Zhao et al, 2019, 2020, 2021), sand cays (Hilton et al, 2019), beaches with large woody debris (Grilliot, Walker, & Bauer, 2018; Grilliot, Walker, & Bauer, 2019), and beach scarped ridges (Smyth & Hesp, 2015). These studies have contributed to our understanding of flow–form–sand transport relationships in a wide range of aeolian situations.…”
Section: Introductionmentioning
confidence: 99%